Globalized and localized marketing approach for hospitality industry : case study of Sands Resorts Macao - Liao, Xiaoling (2020)
The hospitality industry is usually regarded in the centre of the globalization of international business. As hotels or resorts increasingly extend their properties in multicultural markets, in which China is perceived as one of the most potential markets, this study will learn how the globalized and localized marketing approach should be pursued, which is needed for multinational hotels chains to gain more market share in China. The aim of the study is to explore the marketing promotion campaigns of an American resort in China to understand the approaches the organisation utilises to succeed on the Chinese market. An in-depth case study of Sands Resorts Macao’s marketing campaigns in Chinese market will be conducted in the light of Segmentation, Targeting and Positioning (STP) theory. The case study will try to present the practical and empirical insights for researchers and marketers. This study revealed that international hospitality brands could leverage globalized marketing strategy to make its brand easily recognized, and use localized marketing strategy to do concrete emotion driven among mainland Chinese tourists and raise brand awareness in Chinese market. The findings will provide significant insight and implications for multinational hotels and resorts brands which are ambitious to extend Chinese market or improve brand awareness in Chinese market.